KERAGAMAN DAN SUMBER GEN KETAHANAN VARIETAS PADI LOKAL TERHADAP PATOGEN Pyricularia grisea PENYEBAB PENYAKIT BLAS - Santoso, Santoso; Nasution, Anggiani; Yunani, Nani (BPFP Universitas Bengkulu, 2020)
[DIVERSITY AND THE SOURCE OF RESISTANCE GENE OF LOCAL RICE VARIETIES ON THE PATHOGENIC OF Pyricularia grisea CAUSE OF BLAST DISEASE]. Local rice varieties are known to have resistance or source of genes to pests even though their productivity yield is low. The pathogen of Pyricularia grisea is a cause of blast disease, which is one of the obstacles in rice production. The research aims to characterize the resistance of local rice varieties to the pathogen of P. grisea and to evaluate the virulence level of P. grisea pathogens against local rice varieties. A total of 100 local rice varieties and check varieties are susceptible and resistant namely Kencana Bali and Situ Patenggang tested their resistance to 4 dominant pathogenic of P. grisea i.e. races 033, 073, 133 and 173. Inoculation was carried out on stages 4-5 leaves or 18-21 days after seedling in a green house. The results showed a high genetic diversity of local rice varieties against pathogenic races 033, 073, 133 and 173. Based on the response of local rice varieties resistance i.e. moderately resistant (MR), resistant (R) and susceptible (S) to pathogenic races 033, 073 , 133 and 173 obtained 45 resistance response patterns. Cere Bereum varieties which are local rice varieties from West Java and Situ Patenggang resistant check varieties have a resistant response to 4 P. grisea pathogenic races used. A number of local rice varieties also show a resistant and moderately resistant response to the four pathogenic races used include Siam 11, Pare Siriendah, Menyan, Cere Manggu and Enud-Rawa Bogo. Local rice varieties Djedah and Padi Hitam (2) are local rice varieties that have a specific response of resistant or moderately resistant to race 173. Race 133 and 173 have higher virulence rates than those of races 033 and 073 on local rice varieties. The results of this study indicate that there is a great potential for the utilization of local rice varieties, as a source of resistance genes for blast disease for the assembly of rice varieties that are resistant to blast disease.